2012
DOI: 10.1371/journal.pgen.1002568
|View full text |Cite
|
Sign up to set email alerts
|

Neurobeachin, a Regulator of Synaptic Protein Targeting, Is Associated with Body Fat Mass and Feeding Behavior in Mice and Body-Mass Index in Humans

Abstract: Neurobeachin (Nbea) regulates neuronal membrane protein trafficking and is required for the development and functioning of central and neuromuscular synapses. In homozygous knockout (KO) mice, Nbea deficiency causes perinatal death. Here, we report that heterozygous KO mice haploinsufficient for Nbea have higher body weight due to increased adipose tissue mass. In several feeding paradigms, heterozygous KO mice consumed more food than wild-type (WT) controls, and this consumption was primarily driven by calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Heterozygous mice for a gene trap disruption of Nbea were, surprisingly, not smaller than normal as described for the heterozygous mice generated by Su et al , and they showed no behavioral phenotype, as was suggested by the human autism studies. Instead, the heterozygous Nbea gene trap mice develop mild obesity due to increase in adipose tissue associated with increased eating . The obesity and over‐eating was responsive to leptin and naltrexone, suggesting that this form of obesity involved neurological signals .…”
Section: Human Bdcps and Associated Human Disordersmentioning
confidence: 59%
“…Heterozygous mice for a gene trap disruption of Nbea were, surprisingly, not smaller than normal as described for the heterozygous mice generated by Su et al , and they showed no behavioral phenotype, as was suggested by the human autism studies. Instead, the heterozygous Nbea gene trap mice develop mild obesity due to increase in adipose tissue associated with increased eating . The obesity and over‐eating was responsive to leptin and naltrexone, suggesting that this form of obesity involved neurological signals .…”
Section: Human Bdcps and Associated Human Disordersmentioning
confidence: 59%
“…The mammalian orthologues of rg are Neurobeachin ( Nbea ) and LPS-responsive, beige-like anchor ( Lrba ) (Volders et al 2012). Mice heterozygous for an Nbea null allele increased food intake and white adipose, while in humans, variants in Nbea are significantly associated with an increased body mass index (Olszewski et al 2012). NBEA interacts with the glycine receptor β subunit in the central nervous system, where it may help traffic neurotransmitters (del Pino et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human mutations in LRBA cause a syndrome of immunological abnormalities (Lopez-Herrera et al, 2012). Heterozygous rearrangements in the human NBEA gene were detected in patients with autism (Castermans et al, 2003) or with multiple myeloma (O'Neal et al, 2009), and reduced Nbea expression causes overweight patients (Olszewski et al, 2012).…”
Section: Less Functional Neurotransmitter Receptors At Nbea Ko Synapsesmentioning
confidence: 99%